I Funny: School of Laughs - Book 5 - Patterson, James 1947-; Grabenstein, Chris; Raymond, Emily, 1972-; Tejido, Jomike (New York : JIMMY Patterson Books/Little, Brown and Company, 2017)
A wheelchair-bound middle school teacher tries to teach a comedy class to bored students.
Keywords: Comedians -- Juvenile fiction; People with disabilities -- Juvenile fiction; Wheelchairs -- Juvenile fiction; Middle schools -- Juvenile fiction; Comedians -- Fiction; People with disabilities -- Fiction; Wheelchairs -- Fiction; Middle schools -- Fiction; Humorous Stories